2020
DOI: 10.1111/bph.15004
|View full text |Cite
|
Sign up to set email alerts
|

Morphine‐induced respiratory depression is independent of β‐arrestin2 signalling

Abstract: Background and Purpose: GPCRs can signal through both G proteins and β-arrestin2.For the μ-opioid receptor, early experimental evidence from a single study suggested that G protein signalling mediates analgesia, whereas β-arrestin2 signalling mediates respiratory depression and constipation. Consequently, for more than a decade, much research effort has been focused on developing biased μ-opioid agonists that preferentially target G protein signalling over β-arrestin signalling, as it was believed that such dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
170
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 25 publications
15
170
2
Order By: Relevance
“…This would be akin to providing a lower dose of standard opioid drugs. Regardless, our results, along with similar data from another recent study 18 , call into question the foundational model that Arrb2 selectively mediates OIRD and suggest that in the future, we must reconsider and reinvestigate the mechanism of biased agonism in vivo. Animals Arrb2 20 has been described.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This would be akin to providing a lower dose of standard opioid drugs. Regardless, our results, along with similar data from another recent study 18 , call into question the foundational model that Arrb2 selectively mediates OIRD and suggest that in the future, we must reconsider and reinvestigate the mechanism of biased agonism in vivo. Animals Arrb2 20 has been described.…”
Section: Discussionsupporting
confidence: 56%
“…More recently, however, results of these studies have been called into question 17,18 , prompting us to independently investigate the underlying necessity of Arrb2 in mediating ORID.…”
Section: Introductionmentioning
confidence: 99%
“…The whole concept which states that G-protein biased agonists of the MOR that do not recruit β-arrestin could significantly improve the therapeutic window and are less prone to the development of classical opioids side effects still remains under very sensitive scrutiny. Indeed, several recent studies ask for very careful consideration of the in vitro/in vivo data, given that β-arrestin 2 signaling might not be directly or indirectly involved in opioid-induced respiratory depression, constipation, or withdrawal [ 27 , 53 , 54 ]. Among the most important findings, the respiration of morphine was found to be β-arrestin 2-independent.…”
Section: Mor Biased Agonismmentioning
confidence: 99%
“…As an example, a "β-blocker" that antagonizes G protein activation but recruits β-arrestin has been found to increase survival rates in patients suffering from heart failure (1). At the μ-opioid receptor G protein signaling has been proposed to be responsible for analgesia, with side effects such as respiratory depression resulting from arrestin-mediated signaling (2,3), although this paradigm has recently been challenged (4)(5)(6). We have demonstrated that β-arrestin recruitment to the dopamine D2 receptor in indirect pathway neurons in the ventral striatum leads to enhanced locomotion, whereas G protein signaling is necessary for incentive behavior (7), further emphasizing the potential importance of biased signaling in more targeted therapeutics.…”
Section: Introductionmentioning
confidence: 99%